Factors influencing overbreak volumes in drill-and-blast tunnel excavation. A statistical analysis applied to the case study of the Brenner Base Tunnel – BBT. (November 2020) - Foderà, G.M.; Voza, A.; Barovero, G.; Tinti, F.; Boldini, D.
Highlights: This paper investigates the overbreak in tunnels excavated with the drill-and-blast method. The study proposes an operative methodology to estimate the overbreak volumes. The technical overbreak can be distinguished from the geological overbreak from the inspection of the excavated surfaces. The approach was implemented during the construction of a portion of the Brenner Base Tunnel. An empirical model for overbreak prediction, based on the Rock Mass Rating index and the length of blast-holes, is proposed. Abstract: This paper deals with the analysis of overbreak in tunnels excavated with the drill-and-blast method. The overbreak phenomenon has many negative impacts on tunnelling organisation and economy and its precise assessment plays a fundamental role in the process of construction optimisation. The study proposes an operative methodology to estimate overbreak volumes and to distinguish so-called technical overbreak, mainly related to drill-and-blast design and execution, from geological overbreak, typically influenced by rock-mass characteristics. The approach was developed and implemented during the excavation of the Brenner Base Tunnel (BBT) and was based on the interpretation of tunnel laser scanning surveys and high-resolution images of the excavated surfaces. The analysis of more than 1, 800 m of excavation from three different tunnels of the BBT system allowed to identify the main factors influencing the technical and the geological overbreak. An empirical model for overbreak prediction, based on the Rock Mass Rating index and the length of blast holes, is subsequently presented and validated in the last part of the paper.